2019
DOI: 10.1186/s13662-019-2009-4
|View full text |Cite
|
Sign up to set email alerts
|

Hopf bifurcation of a heroin model with time delay and saturated treatment function

Abstract: In this paper, local stability and Hopf bifurcation of a delayed heroin model with saturated treatment function are discussed. First of all, sufficient conditions for local stability and existence of Hopf bifurcation are obtained by regarding the time delay as a bifurcation parameter and analyzing the distribution of the roots of the associated characteristic equation. Directly afterward, properties of the Hopf bifurcation, such as the direction and stability, are investigated with the aid of the normal form t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…( 2015 ), Huang and Liu ( 2013 ), Liu and Zhang ( 2011 ), Wang et al. ( 2011 ), Wangari and Stone ( 2017 ), Zhang and Wang ( 2019 ), Maji ( 2021 ), White and Comiskey ( 2007 ), Yang et al. ( 2016a ), Elragig ( 2013 ), Friedman ( 2008 ), Guo et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 2015 ), Huang and Liu ( 2013 ), Liu and Zhang ( 2011 ), Wang et al. ( 2011 ), Wangari and Stone ( 2017 ), Zhang and Wang ( 2019 ), Maji ( 2021 ), White and Comiskey ( 2007 ), Yang et al. ( 2016a ), Elragig ( 2013 ), Friedman ( 2008 ), Guo et al.…”
Section: Discussionmentioning
confidence: 99%
“… 2015 ; Huang and Liu 2013 ; Liu and Zhang 2011 ; Wang et al. 2011 ; Wangari and Stone 2017 ; Zhang and Wang 2019 ; Maji 2021 ). In 1979, an exponential model has been simplified from Kermack and McKendrick’s disease model by MacKintosh and Stewart ( 1979 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there should be a period for a drug user in treatment before he relapses into the physiological addicts due to the effect of treatment and his self-control. With an eye to such considerations and motivated by the work of some other dynamical systems with time delay [26][27][28][29][30], we investigate a more realistic synthetic drugs transmission model as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the previous work contributions, Zhang and Wang acquired a delayed heroin model in 2019. The authors studied the impact of the time delay on heroin model and concluded that the addicts are not cured quickly, rather they need a time period [19]. Random perturbations were introduced in the deterministic heroin epidemic model by Wei, Yang, and Li in [20].Although huge improvements have been made towards the utilization of mathematical methods to model infectious disease, very little efforts have been made to impose this work on heroin epidemic models.…”
mentioning
confidence: 99%